Calcium, calmodulin and calcineurin - Bolsover, Stephen (Henry Stewart Talks, 2007)
Calmodulin is highly conserved, Calmodulin structure, EF hand proteins, Calcium binding, Calmodulin targets, Mechanism of calmodulin action, Calmodulin-dependent protein kinases, Calmodulin dependent protein kinase II autonomy, Calcineurin structure and activation, Action of cyclosporin, NFAT signaling, Phosphatases downstream of calcineurin, Differential responses of calmodulin-dependent protein kinase II and calcineurin to calcium signals
Archived at 2016/06/22